2014
DOI: 10.1016/j.ecoleng.2014.09.046
|View full text |Cite
|
Sign up to set email alerts
|

Algal community analysis in a waste stabilisation pond

Abstract: Este documento contiene información de prueba. Contáctese con el administrador del Centro para el acceso al documento originar del registro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 24 publications
0
10
0
5
Order By: Relevance
“…25 Also, the results of the optimized maximum specific growth rates indicated a higher value for Chlorella compared with Scenedesmus. This was not expected since it was found in Pham et al 10 that both species were abundant to a similar extent in the pond. However, the optimized values in this research are the maximum growth rates for autotrophic growth.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…25 Also, the results of the optimized maximum specific growth rates indicated a higher value for Chlorella compared with Scenedesmus. This was not expected since it was found in Pham et al 10 that both species were abundant to a similar extent in the pond. However, the optimized values in this research are the maximum growth rates for autotrophic growth.…”
Section: Discussionmentioning
confidence: 64%
“…This WSP treats the municipal wastewater from 400 000 inhabitants of the city. Two of the most dominant microalgal species in the WSP were Chlorella and Scenedesmus . Therefore, these species were used during the experiments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estas generan efluentes que pueden utilizarse para el reciclaje de nutrientes en la agricultura ó la recuperación de suelos [3]. Su diseño, favorece el desarrollo de una amplia variedad de microorganismos y procesos físicos, químicos y biologicos [4] que al interrelacionarse favorecen la depuración de las aguas contaminadas [5]. A pesar de sus ventajas, una de sus deficiencias más importante, es la elevada concentración de sólidos suspendidos (SS) en el efluente [6].…”
Section: Introductionunclassified
“…The spatial variation of oxygen is associated with the change in algal community composition and distribution between different ponds and different locations within each individual pond [9]. Pham et al [10] observed higher values of algal abundance, richness and diversity in maturation ponds (MPs) compared to FPs and lower biovolumes of motile algal species in the inlet compared to the outlet of Ucubamba WSP system in Cuenca (Ecuador). Furthermore, as a result of light attenuation, the algal photosynthesis in FPs can locate only at 20-30 cm from the water surface while that value is around 60 cm for clear and less turbid MPs [11].…”
Section: Introductionmentioning
confidence: 99%